2017
DOI: 10.1038/ncomms15506
|View full text |Cite
|
Sign up to set email alerts
|

Highly indistinguishable and strongly entangled photons from symmetric GaAs quantum dots

Abstract: The development of scalable sources of non-classical light is fundamental to unlocking the technological potential of quantum photonics. Semiconductor quantum dots are emerging as near-optimal sources of indistinguishable single photons. However, their performance as sources of entangled-photon pairs are still modest compared to parametric down converters. Photons emitted from conventional Stranski–Krastanov InGaAs quantum dots have shown non-optimal levels of entanglement and indistinguishability. For quantum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
281
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(303 citation statements)
references
References 60 publications
(128 reference statements)
13
281
4
Order By: Relevance
“…Quantum bit (qubit), as the fundamental building block for quantum computing and quantum network, can take various materialized forms in reality as long as the system comprises two distinct quantum states that can be coherently superpositioned, for example, the atomic clock states of trapped ion, the orthogonal polarization states of photon, the spin states of electron confined in a solid‐state potential, the superconducting state of micro‐circuit, and the emergent Majorana bound states featuring topological protection . All these candidates possess a finite coherence time imposed by the dephasing processes originating from the inevitable coupling to the host environment.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum bit (qubit), as the fundamental building block for quantum computing and quantum network, can take various materialized forms in reality as long as the system comprises two distinct quantum states that can be coherently superpositioned, for example, the atomic clock states of trapped ion, the orthogonal polarization states of photon, the spin states of electron confined in a solid‐state potential, the superconducting state of micro‐circuit, and the emergent Majorana bound states featuring topological protection . All these candidates possess a finite coherence time imposed by the dephasing processes originating from the inevitable coupling to the host environment.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the Coulomb interaction between the QD‐confined charges, the X energy is typically separated from the XX energy by a few meV. The pump laser energy is thus not resonant with either line and can be effectively suppressed with sharp notch filters . Recent studies have shown that the X and XX can be coherently populated with near‐equal efficiencies, showing entanglement fidelities comparable to that of SPDC sources .…”
Section: Advanced Qd Excitation Methodsmentioning
confidence: 99%
“…d) Cross‐sectional 3D view of an AFM image of a nanohole in an AlGaAs layer, along with the sketch of the sample structure and the top view of the AFM measurement result; e–f) microphotoluminescence spectrum of a representative QD under non‐resonant excitation (e) and resonant two‐photon excitation (f). Reproduced with permission . Copyright 2017, Springer Nature.…”
Section: Advanced Epitaxial Growth Technology For Novel Single Qdsmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approach is to pursue intracavity SPDC as discussed in the introduction, but we believe that a better option is to use even shorter lifetime quantum dots such as the GaAs/AlGaAs system, where quantum dots are grown by droplet epitaxy. Early results show radiative lifetimes of less than 250 ps [26,27] and high indistinguishability without any filtering or shaping. Table 1.…”
Section: Discussion and Outlookmentioning
confidence: 99%